2018
DOI: 10.1126/scisignal.aan0949
|View full text |Cite
|
Sign up to set email alerts
|

SILAC identifies LAD1 as a filamin-binding regulator of actin dynamics in response to EGF and a marker of aggressive breast tumors

Abstract: Mutations mimicking growth factor-induced proliferation and motility characterize aggressive subtypes of mammary tumors. To unravel currently unknown players in these processes, we performed phosphoproteomic analysis on untransformed mammary epithelial cells (MCF10A) that were stimulated in culture with epidermal growth factor (EGF). We identified ladinin-1 (LAD1), a largely uncharacterized protein to date, as a phosphorylation-regulated mediator of the EGF-to-ERK pathway. Further experiments revealed that LAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 59 publications
4
55
0
Order By: Relevance
“…Most of these genes have been shown to be dysregulated in breast cancer or during epithelial-mesenchymal transition. Indeed, LAD1 has been associated with aggressive breast tumours, 41 COL17A1 is underexpressed in breast cancer and overexpressed in head and neck squamous cell carcinoma, lung squamous cell carcinoma and lung adenocarcinoma 42 and FERMT1 is a known mediator of epithelial-mesenchymal transition in colon cancer. 43 Cancer-risk SNPs preferentially target cancer genes We expected that cancer-risk SNPs might be preferentially associated with genes known to be involved in cancer development and progression.…”
Section: Cancer-risk Snps Regulate Cancer-related Biological Functionsmentioning
confidence: 99%
“…Most of these genes have been shown to be dysregulated in breast cancer or during epithelial-mesenchymal transition. Indeed, LAD1 has been associated with aggressive breast tumours, 41 COL17A1 is underexpressed in breast cancer and overexpressed in head and neck squamous cell carcinoma, lung squamous cell carcinoma and lung adenocarcinoma 42 and FERMT1 is a known mediator of epithelial-mesenchymal transition in colon cancer. 43 Cancer-risk SNPs preferentially target cancer genes We expected that cancer-risk SNPs might be preferentially associated with genes known to be involved in cancer development and progression.…”
Section: Cancer-risk Snps Regulate Cancer-related Biological Functionsmentioning
confidence: 99%
“…This study is primarily focused on chemotaxis of a metastatic breast cancer cell, MDA-MB-231, under chemotactic EGF gradients. Although the effects of EGF has been investigated extensively (38,39), multiple facets of EGF still continue to be identified (40)(41)(42)(43). EGF promotes actin nucleation for Mena invasive-expressed cells (40) and regulates intracellular mechanical responses related to ladinin-1 (41,42).…”
Section: Introductionmentioning
confidence: 99%
“…Although the effects of EGF has been investigated extensively (38,39), multiple facets of EGF still continue to be identified (40)(41)(42)(43). EGF promotes actin nucleation for Mena invasive-expressed cells (40) and regulates intracellular mechanical responses related to ladinin-1 (41,42). Moreover, breast cancer cells within hydrogels exhibit different responses to EGF gradients and EGF receptor (EGFR) inhibitors depending upon cell types (43).…”
Section: Introductionmentioning
confidence: 99%
“…7b). Previous studies have reported that LAD1, C1ORF106, PVRL4, and KCNK5 are upregulated in cancer cells [82][83][84][85]. Furthermore, LAD1 has been reported as a filament-binding regulator and also regulates EGF signaling-mediated breast cancer tumorigenesis [82].…”
Section: Cross-cancer Analysis Of Prominin Mutations and Copy Number mentioning
confidence: 98%